The Problem-Based Threshold: Shifting Pre-Service Teachers' Thinking About Mathematics Instruction. Issue 1 (2nd January 2020) - King, Barbara; Bartman, Jennifer; Gil, Indira
Abstract: The purpose of the mathematics methods course where this study took place was to support pre-service teachers (PSTs) as their thinking about instruction transitioned from a traditional, teacher-centered approach to a more problem-based, student-centered approach, and to guide them as they developed strategies for teaching through problem solving. We used writing assignments to prompt PSTs to think critically about mathematics instruction. We then analyzed their writing to determine whether PSTs' thinking about instruction changed throughout the course. The results show that at the beginning of the course, PSTs' thinking was deeply rooted in traditional views, but that as the course progressed, their thinking shifted toward more problem-based views. Additionally, we examined PSTs' writing to look for instances where their traditional thinking interfered with their emerging problem-based ideas about instruction. Determining the ways PSTs' struggled to develop problem-based views has significant implications for mathematics methods course design and teaching practices.